Pencapaian vaksinasi COVID-19 pada anak usia 12 - 18 tahun periode Agustus - September 2021 di Puskesmas Kelurahan Cililitan - Luh Kadek Shastri Utami Wijayanti; Aan Kurniawan; Amalia Farahtika Srikandi; Jovian Lutfi Daniko; Setya Bayu Kurniawan (DiscoverSys Inc., 2021)
Background: The morbidity and mortality rate of COVID-19 in Indonesia is increasing. Various efforts have been made to prevent the transmission process which is expected to have a significant impact in reducing morbidity and mortality due to COVID-19. One of the steps taken by the Indonesian government is the implementation of COVID-19 vaccination for the entire community. The COVID-19 vaccination program in Indonesia is planned to run from February 2021 to March 2022, where one of the targets for COVID-19 vaccination is children.Aim: The study was conducted to assess the achievement of COVID-19 vaccination in children aged 12-18 years at the Cililitan Urban Village Health Center for the period August - September 2021.Method: This research is a cross-sectional study conducted at the Cililitan Urban Village Health Center in October 2021. The research sample was all vaccine participants at the Cililitan Urban Village Health Center who attended the first and second vaccines with a total sampling technique. The research data were obtained through documentation of vaccination records at the Cililitan Urban Village Health Center. The data obtained are presented as part of personal data and vaccination achievements in graphic form.Result: The recording of the results of vaccination services is carried out electronically through the information system for one COVID-19 vaccination data, namely the Pcare application which is carried out during the COVID-19 vaccination service. The COVID-19 vaccination program for children aged 12-18 years has been implemented since July 1, 2021. The Cililitan Urban Village Health Center area has 16 Neighborhood Units with a total population of children aged 12-18 years as many as 2955 people. The results of the achievements of children aged 12-18 years in the Cililitan Urban Village area for the period August - September 2021 who were vaccinated with the first dose were 13.73% and the second dose vaccinated was 24.53%.Conclusion: The Cililitan Urban Village Health Center has run a vaccination program for children aged 12-18 years, but the vaccination coverage in August-September 2021 has not reached the target of 50%. Latar Belakang: Angka kesakitan dan kematian COVID-19 di Indonesia semakin meningkat. Berbagai upaya dilakukan untuk mencegah proses penularan yang diharapkan berdampak signifikan dalam menurunkan angka kesakitan dan kematian akibat penyakit COVID-19. Salah satu langkah yang diambil dari pemerintah Indonesia yaitu pelaksanaan vaksinasi COVID-19 untuk seluruh masyarakat. Program vaksinasi COVID-19 di Indonesia direncanakan berlangsung dari bulan Februari 2021 hingga Maret 2022, dimana salah satu sasaran vaksinasi COVID-19 adalah anak - anak.Tujuan: Penelitian dilaksanakan untuk melakukan penilaian terhadap pencapaian vaksinasi COVID-19 pada anak usia 12 – 18 tahun di Puskesmas Kelurahan Cililitan periode Agustus - September 2021.Metode: Penelitian ini merupakan studi potong lintang yang dilaksanakan di Puskesmas Kelurahan Cililitan pada bulan Oktober 2021. Sampel penelitian adalah semua peserta vaksin Puskesmas Kelurahan Cililitan yang hadir vaksin pertama dan kedua dengan teknik total sampling. Data penelitian didapatkan melalui dokumen pencatatan vaksinasi di Puskesmas Kelurahan Cililitan. Data yang diperoleh disajikan menjadi bagian data diri dan capaian vaksinasi dalam bentuk grafik.Hasil: Pencatatan hasil pelayanan vaksinasi dilakukan secara elektronik melalui sistem informasi satu data vaksinasi COVID-19, yaitu aplikasi Pcare yang dilakukan saat pelayanan vaksinasi COVID-19 berlangsung. Program vaksinasi COVID-19 untuk anak usia 12 – 18 tahun sudah dilaksanakan sejak 1 Juli 2021. Wilayah puskesmas memiliki 16 Rukun Warga dengan total populasi anak usia 12 – 18 tahun sebanyak 2955 orang. Hasil capaian anak usia 12 – 18 tahun di wilayah Kelurahan Cililitan periode Agustus – September 2021 yang tervaksinasi dosis I sebesar 13,73% dan tervaksinasi dosis II sebesar 24,53%.Kesimpulan: Puskesmas Kelurahan Cililitan telah menjalankan program vaksinasi anak usia 12 – 18 tahun, namun cakupan vaksinasi pada bulan Agustus – September 2021 belum mencapai target hingga 50%.